Effect of Supplementation of Aloe Vera Juice on Growth Performance of Japanese Quails - P., Jogeswar; D, Sreekumar; P, Ponnuvel; P.K., Mandal; R, Ganesan; N, Elanchezhiyan (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
An experiment was carried out in 300 Namakkal strain of Japanese quails from day-old to five weeks of age to study the effect of supplementation of Aloe vera (Aloe barbadensis) juice at different concentrations through drinking water on growth performance.The birds were divided into four treatment groups with three replicates in each treatment and each replicate had 25 birds. The four experimental groups consisted of T0 (control), T1, T2 and T3 supplemented with Aloe vera juice @ 0, 1.0, 1.5 and 2.0%, respectively, in drinking water. The body weight of quails was measured weekly from hatch till five weeks of age and feed consumption and feed conversion ratio were calculated weekly. Mortality and livability were recorded daily and weekly, respectively. The results revealed a significant difference (p <0.05) in body weight and body weight gain among the groups supplemented with Aloe vera juice and control group. The cumulative feed consumption showed a significant difference (p <0.05) in first to fourth week, whereas on the fifth week there was no significant difference between groups. A significant difference (p <0.05) in feed conversion ratio among all groups supplemented with aloe vera juice and control group was observed from first to fifth week of age. Livability was not affected in quails by Aloe vera juice supplementation. Aloe vera juice supplementation (1.5%) was found beneficial in improving the overall growth performance of Japanese quails.